(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
This research intended to analyze the impact of the invited speakers on students’ confidence in speaking English and the causes of students’ self-confidence insufficiency in speaking English. This research was qualitative. This research was conducted in STIKes Bina Cipta Husada Purwokerto. Two public health students were the subjects of this research. Observation and interview were conducted to collect the data. Then, the data was analyzed using three steps such as data reduction, data display, and conclusion drawing. The result obtained that there are some impacts of the invited native speakers on students’ self-confidence in speaking English such as increasing students’ confidence, evaluating themselves to communicate with others, and increasing students’ vocabulary and pronunciation. Meanwhile, the causes of students’ self-confidence insufficiency in speaking English such as lack of pronunciation and vocabulary, and also fear of making mistakes.